2013
DOI: 10.1371/journal.pone.0065224
|View full text |Cite
|
Sign up to set email alerts
|

The Enterococcus faecium Enterococcal Biofilm Regulator, EbrB, Regulates the esp Operon and Is Implicated in Biofilm Formation and Intestinal Colonization

Abstract: Nowadays, Enterococcus faecium is one of the leading nosocomial pathogens worldwide. Strains causing clinical infections or hospital outbreaks are enriched in the enterococcal surface protein (Esp) encoding ICEEfm1 mobile genetic element. Previous studies showed that Esp is involved in biofilm formation, endocarditis and urinary tract infections. In this study, we characterized the role of the putative AraC type of regulator (locus tag EfmE1162_2351), which we renamed ebrB and which is, based on the currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…The enterococcal surface protein Esp (EfmE1162_2353) was only identified in TSBg. This is in line with a recent study where it was shown that expression of Esp in BHI was very low compared to growth in TSBg . Esp is considered a virulence factor and can be specifically linked to nosocomial clonal lineages that are genetically distinct from indigenous commensal E. faecium strains .…”
Section: Resultssupporting
confidence: 90%
“…The enterococcal surface protein Esp (EfmE1162_2353) was only identified in TSBg. This is in line with a recent study where it was shown that expression of Esp in BHI was very low compared to growth in TSBg . Esp is considered a virulence factor and can be specifically linked to nosocomial clonal lineages that are genetically distinct from indigenous commensal E. faecium strains .…”
Section: Resultssupporting
confidence: 90%
“…For example, EpaX, an enzyme involved in the synthesis of the surface polysaccharide Epa was found to be critical for GIT colonization by E. faecalis (4). Both the biofilm transcription regulator EbrB and PtsD, a subunit of an uncharacterized phosphotransferase system, were observed to promote colonization by E. faecium (5,6). The genes encoding EpaX, EbrB, and PtsD are carried on mobile genetic elements and/or are enriched in infection-causing clinical enterococcal strains relative to commensal strains and are therefore not part of the core enterococcal genome.…”
Section: Discussionmentioning
confidence: 99%
“…biofilm formation, sugar transport, and the synthesis of cell wall polysaccharides, to promote GIT colonization (4)(5)(6). The genes identified in these studies are located on mobile genetic elements or are enriched in clinical isolates, suggesting that they enhance GIT colonization under some circumstances but do not represent the essential determinants of GIT colonization in the core enterococcal genome that evolved over millions of years to enable enterococci to colonize the GIT.…”
mentioning
confidence: 99%
“…Given the known role of c-di-GMP in biofilm formation, we tested the biofilm formation of each mutant under two growth conditions used routinely in our laboratory. The first, glucose supplemented with Casamino Acids (glucoseϩCAA), is the standard assay medium used in most of our previously reported studies (16,17), and glucose is a common growth substrate used by many groups studying biofilm formation (48)(49)(50)(51). The second substrate analyzed is arginine, one of the few carbon sources which P. aeruginosa can ferment and which we have shown previously boosts the levels of c-di-GMP by ϳ4-fold compared to growth on glucoseϩCAA (52).…”
Section: Only Proteins (Pa14_12810 [Rocr] and Pa14_59790 [Pvrr]) Twomentioning
confidence: 99%